ANALYSIS OF SOME ENGLISH IDIOMS CONTAINING POPULAR PROPER NAMES - Mirzo Makhmudovich Tursunov (Journal Park Publishing, 2022)
This article deals with one of the most essential issues in modern linguistics: phraseological units. Phraseological units play an essential role in every language as they are able to describe real cultural and historical image of the nation based on the speech acts of those who use the language. Idioms that contain this or that proper name can tell us more data about the nation’s culture and history. Any human being is given a name when he comes to the world and in most cases that name has got some related story how it started being used and what hidden information it keeps inside. Every nation has got some proper names that are popular cause of some reasons; they take us back to some historical event or cultural, traditional ritual dating back to very far. Usually those names are connected with the religious beliefs, rituals, rules and regulations kept in this or that society as sacred principles. Some proper names in idioms can belong only to that nation’s cultural heritage. In this article we are going to analyze some idioms containing famous English proper names to see what they may hide related to culture or history as lexical units playing essential roles in vocabulary of the language.
Keywords: speech act; linguistic category; anthropocentricity